Thinning response functions for single trees of Common oak (Quercus Robur L.) - Claesson, Svante (2012)
Functions for estimation of the total thinning response, on the basal area growth for single trees, of Common oak (Quercus robur L.) are presented. The total thinning response is defined as the ratio between basal area growth of a tree affected by thinnings and the hypothetical basal area growth of that same tree unaffected by thinnings. The thinning response functions can isolate the effect, on the basal area growth, of all historical thinnings in a stand, given knowledge of the intensity, time and method of every thinning performed. The functions are estimated by data from southern Sweden.